THE USE OF INNOVATIVE TECHNALOGIAYAS IN TEACHING EDUCATIONAL SCIENCE IN GENERAL SECONDARY SCHOOLS - Nurbayeva Shahsanam (American Journals Publishing, 2022)
We hope that this article will be useful to many of them in the field of scientific observations on the use of innovative technologies in teaching educational science in general secondary schools.
Keywords: innovative technology, educational science, textbook, audiovisual active civil position